Acquisition, ownership and use of natural resources in South Eastern Zimbabwe, 1929-1969 - Ndumeya, Noel (University of the Free State, 2015)
This study examines patterns of natural resources distribution and land use in south eastern Zimbabwe, originally known as Melsetter, and later Melsetter and Chipinga Districts. The study focuses on land utilisation, water, game and indigenous timber uses from 1929 to 1969. Prior to white occupation of this area, Africans owned and used these resources under precolonial communal tenure systems. The means by which these resources were seized, particularly in what became the white settler areas of the Melsetter and Chipinga Highlands, is traced from the mid-1890s onwards. Thereafter changing ownership and land use transformations are examined in detail among the diverse inhabitants of this region. African livelihood experiences during the Great Depression of c 1929-1939 are closely analysed, and their agency is brought out through the ways in which they challenged colonial policy. In the pre-1945 era, although the best land had already been alienated, Africans continued to use these resources as labour tenants. That the Melsetter District had great agricultural potential partly explains why it attracted white settlement as early as the mid-1890s. The study also analyses why, when compared to other white settled districts, for more than fifty years after colonial occupation, Melsetter remained an agriculturally backward and undercapitalised settler region. After the Second World War, parts of the region were transformed by the acquisition of land by corporate timber concerns. In the 1960s, coffee growers who arrived mostly from east Africa settled in parts of this region. By embarking on commercial coffee production, they had a significant impact on the agricultural history of the area. These secondary land acquisitions are explored at three levels; firstly, as a local reflection of changing global political and economic conditions; secondly, the intensive use of land resources, and how this had a direct impact on the Africans who formerly utilised this land as tenants and, thirdly; changing African reactions especially where this led to direct confrontation. These historical developments are examined within the broad context of the heterogeneous societies inhabiting this region.

Hierdie studie ondersoek die verspreidingspatrone van natuurlike hulpbronne en grondgebruik in suidoos Zimbabwe, in die gebied oorspronklik bekend as Melsetter, en later as Melsetter en Chipinga Distrik. Die ondersoek fokus op die gebruik van grond, water, wild en inheemse hout tussen 1929 en 1969. Voordat hierdie area deur Europeërs beset is, het Afrikane hierdie hulpbronne binne ‘n prekoloniale stelsel van gemeenskaplike besit, gebruik. Die manier waarop hierdie hulpbronne buitgemaak is, veral in die latere wit setlaararea van Melsetter en Chipinga Hoogland, word vanaf die middel-1890s ondersoek. Volgende word veranderende patrone van eienaarskap en grondgebruik onder die diverse bewoners van hierdie gebied deeglik ondersoek. Nadere ondersoek word na die bestaanservaringe van Afrikane gedurende die Groot Depressie van ca. 1929 tot 1939 ingestel, en daar word aangedui hoe hul agentskap veral in die manier waarop hulle koloniale beleid uitgedaag het, na vore kom. Alhoewel die beste grondgebied reeds voor 1945 onteien is, het Afrikane as huurarbeiders hierdie hulpbron aanhou benut. Die ryk landboupotensiaal van die Melsetter Distrik bied ‘n gedeeltelike verduideliking vir waarom dié distrik reeds so vroeg as die middel-1890s Europese setlaars gelok het. Hierdie ondersoek analiseer waarom Melsetter, in vergelyking met ander wit setlaarsdistrikte, vir meer as vyftig jaar ná koloniale besetting steeds ‘n landboukundig agterlik en onderkapitaliseerde setlaarstreek was. Ná die Tweede Wêreldoorlog is gedeeltes van die streek deur korporatiewe houtondernemings se verkryging van grond getransformeer. In die 1960s het koffieprodusente, meestal uit Oos-Afrika, hul in dele van die streek gevestig. Kommersiële koffieproduksie sou ‘n belangrike impak op die landboukundige geskiedenis van dié area hê. Hierdie sekondêre proses van grondverkryging word op drie vlakke ondersoek: eerstens, as ‘n plaaslike weerspieëling van globale politieke en ekonomiese toestande; tweedens, in terme van die intensiewe gebruik van grondhulpbronne, en die direkte uitwerking daarvan op die Afrikane wat die grond bewerk het; en, derdens, Afrikane se veranderende reaksies, veral waar dit tot direkte konfrontasie gelei het. Hierdie historiese gebeurtenisse word binne die breë konteks van die heterogene samelewings wat hierdie streek bewoon, ondersoek.
Thesis (Ph.D. (Centre for Africa Studies))--University of the Free State, 2015
Keywords: Acquisition; Ownership; Land use; Livelihoods; Agency; Labour tenancy; Reserves; Plantations; Coffee; Conflict; Natural resources--Zimbabwe; Land use--Zimbabwe; Natural resources